The Digital Accounting Revolution: How AI and Machine Learning Are Changing the Role of Accountants - Loso judijanto; Muhammad Irfan Aditma; Suhartono Suhartono; Ratih Andaningsih (Oikonomia : Journal of Management Economics and Accounting, 2025)
The development of digital technology, especially Artificial Intelligence (AI) and Machine Learning (ML), has significantly changed the accounting profession from manual work to more efficient and accurate process automation. This automation allows accountants to focus on data analysis and strategic decision-making, but also requires mastery of new digital skills such as data analytics and basic programming. However, current accounting education still relies heavily on conventional methods, resulting in a skills gap between graduates and industry needs. In addition, accounting professional organizations play an important role in encouraging retraining and improving digital competencies for their members. This study uses a qualitative literature study method with thematic analysis to examine the impact of AI and ML on the role of accountants and the responses of educational institutions and the profession to this digital transformation. The findings indicate the need for collaboration between educational institutions, professional organizations, and industry to overcome the challenges of technology adaptation. With joint efforts, the accounting profession can transform into a strategic partner in an increasingly complex and data-driven business world, while providing significant added value in modern financial management.